Exploring the Impact of Global Economic Factors on Corporate Income Tax: Evidence from OECD Countries - Utama, Muhammad Budi; Kurniawan, Panji Rizki (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Corporate income tax is a cornerstone of fiscal policy, with far-reaching implications for economic development and business operations. As governments seek to fund public expenditures and achieve socio-economic goals, the design and implementation of corporate tax regimes are at the center of government policy agendas. On the other hand, companies navigate tax considerations when making decisions in terms of investing, managing operations, and optimizing financial performance. This study aims to examine the factors that affect corporate tax revenue in OECD countries from 2006-2021 using a quantitative approach and the Generalized Method of Moments (GMM) method. As for the findings in this study, foreign direct investment has no effect on corporate tax revenue. Manufacturing value added and trade openness have a positive influence on corporate tax revenue.